N-Chromosome Royal Jelly, Propolis and Bee Pollen Supplementation Improve the Clinical Conditions of COVID-19 Patients: A Randomized Controlled Trial - Atefeh Abedini; Shadi Shafaghi; Zahra Ameri Ahmad; Elmira Javanmardi; Fariba Ghorbani; Babak Sharif-Kashani; Farah Naghashzadeh; Masoud Shafaghi; Melina Moshirpour; Sima Noorali; Hoda Hakimian; Mohammad Sadegh Keshmiri; et al. (Tehran University of Medical Sciences, 2021)
Royal jelly, propolis, and bee pollen are used for different purposes all around the world according to their anti-inflammatory, antioxidant, and antimicrobial activities. Given that Coronavirus 2019 (COVID-19) is a viral condition accompanied by a dysregulated inflammatory response in the body, we intend to evaluate the effects of natural supplementations on the disease course. A randomized, open-label, controlled trial was conducted among 50 definitive cases of COVID-19. These patients were randomly assigned into control and intervention groups. Royal Jelly, propolis, and bee pollen were prescribed to patients in the intervention group (n = 24) in addition to conventional treatment; while the control group only received the standard treatment (n = 26). At the end of the study, functional class improved in both groups, but this change was more pronounced in the intervention group (p < 0.05). Moreover, total symptoms duration and the time to return to work were significantly reduced in the intervention group (p < 0.05). Although royal jelly, propolis, and bee pollen are not definitive treatments in COVID-19 patients, they can be used as an adjuvant treatment to limit disease symptoms and virus propagation.